2014
DOI: 10.1007/s13277-014-2025-7
|View full text |Cite
|
Sign up to set email alerts
|

Triple-negative and luminal A breast tumors: differential expression of miR-18a-5p, miR-17-5p, and miR-20a-5p

Abstract: New concepts in epigenetics, microRNAs, and gene expression analysis have significantly enhanced knowledge of cancer pathogenesis over the last decade. MicroRNAs (miRNAs) are a class of non-coding RNAs that regulate gene expression by base pairing with target messenger RNAs (mRNAs), resulting in the repression of translation or the degradation of mRNA. To compare the carcinogenic process in tumors with different prognoses, we used real-time RT-PCR to evaluate the miRNA expression profiles of 24 triple-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 42 publications
4
38
1
Order By: Relevance
“…Li et al . demonstrated that down‐regulation of endogenous miR‐17‐5p suppressed the migration and invasion of MDA‐MB‐231 cells by targeting HBP1 and subsequent activation of Wnt/β‐caten 39, 40. These findings suggest that the differences in the expression of miR‐17‐92 cluster will explain the phenotypic differences between these molecular subtypes of tumours.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Li et al . demonstrated that down‐regulation of endogenous miR‐17‐5p suppressed the migration and invasion of MDA‐MB‐231 cells by targeting HBP1 and subsequent activation of Wnt/β‐caten 39, 40. These findings suggest that the differences in the expression of miR‐17‐92 cluster will explain the phenotypic differences between these molecular subtypes of tumours.…”
Section: Resultsmentioning
confidence: 85%
“…Calvano et al . 39 used real‐time RT‐PCR to evaluate the miRNA expression profiles of formalin‐fixed paraffin‐embedded BC tissue. It was found that the expression of miR‐17‐5p, miR‐18a‐5p and miR‐20a‐5 in the triple‐negative tumours (ER−, PR− and HER2−) was higher that of luminal A samples.…”
Section: Resultsmentioning
confidence: 99%
“…Overall these data suggest miR-34a re-introduction in TNBC shuts down oncogenic signaling pathways that affect invasion and proliferation, eventually resulting in cell death by way of cytostasis/senescence. Interestingly, some oncogenic mediators could include non-coding RNAs such as the miR-17/92 cluster, which is known to be elevated in TNBC(2830) and can be downregulated by miR-34a reintroduction(Fig. S2H).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we tried to explore the function of miR-20a-5p in colorectal cancer development and we confirmed that miR-20a-5p was upregulated in CRC tissues, especially metastatic tissues than non-metastatic tissues. Not only in CRC, in breast cancers, miR-20a-5p with miR-17–5p and miR-18a-5p, were also increased in triple-negative compared with the luminal A [22]. In nasopharyngeal carcinoma, overexpressed miR-20a-5p combined with miR-24–3p, miR-891a, miR-106a-5p and miR-1908 formed the exosomes to downregulated the MARK1 signaling pathway to alter cell proliferation and differentiation [23].…”
Section: Discussionmentioning
confidence: 99%